Continuity of midwifery care for Mrs. "G" with Spina Bifida in infant at RD Maternity clinic, Bandung city - Lia Novita; Yanti Herawati (Jurnal EduHealth, 2024)
The incidence of spina bifida varies between two to ten cases per thousand births in various regions worldwide. The Ministry of Health of the Republic of Indonesia has conducted sentinel surveillance. From the results of this surveillance, congenital abnormalities of the nervous system rank second among the most commonly found congenital anomalies in Indonesia, with a percentage of 22.3%. One way to reduce MMR and IMR is by providing continuous midwifery care from pregnancy to family planning through the midwifery management approach. The purpose of providing Continuity of Care is early detection of complications that can threaten life, thus worsening the condition of the mother and baby. The method used during the case study was the Continuity of Care method, which includes collecting subjective and objective data, establishing diagnoses, providing management, and documenting in SOAP format. Visits were conducted 9 times: once during pregnancy, once during childbirth, 4 times during the postpartum period, and 3 times during the newborn period. In the third trimester of pregnancy, the mother experienced discomfort, namely frequent urination and back pain, which could be addressed by providing health education about limiting drinks at night and avoiding caffeinated drinks, as well as providing mechanical body health education. There were no problems found during Mrs. G's delivery. During childbirth, the mother received loving care. During the postpartum period, no problems were found, and visits were conducted according to postpartum care standards. Spina bifida was found in the newborn. The baby received care according to the standard care for normal newborns, followed by referral. No other problems were found in the newborn. The conclusion from the assessment of pregnancy, childbirth, postpartum, and newborn care for Mrs. G was conducted according to midwifery service standards. The problems and discomfort experienced could be addressed. In this case, there was a gap where the patient underwent routine examinations with midwives and doctors, but the case of spina bifida was not detected. This may be due to the fact that spina bifida cannot be detected by midwife examinations, and during ultrasound examinations, it is not clearly visible due to the fetus's position. Midwives are expected to be able to continuously improve the quality of midwifery services and take preventive and management measures for cases of spina bifida.